Antibacterial potential of Ocimum sanctum oils in relation to Enterococcus faecalis ATCC 29212 - Diani Prisinda; Ame Suciati Setiawan; Fajar Fitriadi (Dental Journal (Majalah Kedokteran Gigi), 2018)
Background: Enterococcus faecalis is a Gram-positive cocci present in the root canal due to the failure of endodontic treatment and  pulp tissue necrosis. The ideal root canal medicine offers biocompatible properties, ease of cleaning, absence of tooth staining and non-disruption of the root canal filling process. Basil (Ocimum sanctum) is one of the herbs widely used in salads which produces anti-bacterial, anti-fungal and anti-viral effects. The antibacterial effect of basil results from the eugenol which represents a main component demonstrating antibacterial properties. Basil essential oil has an antibacterial effect on both gram positive and gram-negative bacteria. Purpose: This study aimed to determine whether the essential oils contained in basil leaves offer any antibacterial potential with regard to the growth of Enterecoccus faecalis ATCC 29212. Methods: The research was experimental in nature incorporating a simple random sampling technique. In this study, groups of active substance compounds contained in basil leaves were extracted by distillation in order to obtain the essential oil. Preparation of the test solution involved essence of basil leaf oil at concentrations of 5,000 ppm, 10,000 ppm and 20,000 ppm in methanol solvent. A phytochemical test of basil was subsequently conducted in order to identify the content of the compound. The bacteria in this study was tested utilizing a disc diffusion method (Kirby and Bauer test) by measuring the diameter of the clear zone (clear zone) which is indicative of the bacterial growth inhibition response of antibacterial compounds in the extract. Results: The results of the research into the phytochemical test showed that basil contains phenolic flavonoids, triterpenoids, saponins, tannins which produce a negative result on steroids. The results of this study showed that the basil essential oil inhibition zone present in the Enterecoccus faecalis growth had a diameter of 11.70 mm at a concentration of 20,000 ppm. This concentration therefore proved most effective in relation to Enterococcus faecalis than other concentrations. Conclusion: It can be concluded that essential oils of basil leaves demonstrate anti-bacterial inhibitory properties with regard to Enterococcus faecalis.